1979
DOI: 10.1128/iai.23.3.571-576.1979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacteriocin Production by Streptococcus mutans on the Plaque of Gnotobiotic Rats

Abstract: The effect of bacteriocins produced by strains of Streptococcus mutans on the microbial composition of dental plaque was studied in gnotobiotic rats. In one set of tests, using S. mutans strains T2 and SW31, rats were simultaneously infected with the bacteriocinogenic parent (bac') and corresponding bacmutants, and the relative proportions of each strain present in three different tooth sites were determined at various time intervals after inoculation. Some animals were monoinfected with bac' and bac-strains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Howevet, Aly et al (1) and Shinefield et al (30) demonstrated that a certain strain of S. aureus controls outbreaks of staphylococcal infection in nurseries and treats patients with recurrent staphylococcal fumculosis. Furthermore, since bacteriocins produced by oral bacteria are thought to play an important role in the establishment of the ecosystem (24,33), it may be possible that the bacteriocin presented here is responsible for a part of the control mechanism of microbial ecology.…”
Section: Resultsmentioning
confidence: 99%
“…Howevet, Aly et al (1) and Shinefield et al (30) demonstrated that a certain strain of S. aureus controls outbreaks of staphylococcal infection in nurseries and treats patients with recurrent staphylococcal fumculosis. Furthermore, since bacteriocins produced by oral bacteria are thought to play an important role in the establishment of the ecosystem (24,33), it may be possible that the bacteriocin presented here is responsible for a part of the control mechanism of microbial ecology.…”
Section: Resultsmentioning
confidence: 99%
“…Antagonistic interactions involve the production of inhibitory compounds (bacteriocins, acids, H 2 O 2 , etc.) to inhibit neighbouring cells, and can provide the producer cells with a competitive advantage (120). This might explain, in part, why some bacteria appear in plaque biofilms as discrete clusters of cells ( Fig.…”
Section: Microbial Interactions Cell-cell Communication and Gene Tramentioning
confidence: 99%
“…Cariogenic strains of S. mutans possess the ability to tenaciously colonize smooth surfaces, a property which is primarily dependent on the synthesis of insoluble glucan mediated by glucosyltransferase (GTF) (10). Many of these strains produce bacteriocins, and it is possible that these antibacterial substances may also play a role in colonization (13). The present study describes the transformation of several potential caries-associated properties to mutant strains with chromosomal DNA from cariogenic S. mutans Furthermore, conditions resulting in enhanced frequencies of transformation of this strain are also described.…”
mentioning
confidence: 99%